2003
DOI: 10.1177/000313480306900915
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Physical Examination as a Predictor of Vascular Injury after Penetrating Neck Trauma

Abstract: The policy of routine angiography (ANG) for all penetrating neck wounds results in a high rate of negative studies. The medical records of all patients who presented to Wishard Memorial Hospital and Methodist Hospital of Indiana with penetrating injuries to the neck from January 1992 to April 2001 were reviewed. All patients who were hemodynamically stable underwent four-vessel ANG to evaluate for vascular injury irrespective of findings on physical examination (PE). A total of 216 patients sustained penetrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…The setting of this study is a high‐volume trauma center (~11,000 patients/year) managing a very high number of penetrating trauma victims (~200 PNI/year). Mandatory neck exploration results in a high negative rate (30–89%) in asymptomatic patients [2, 3, 9, 12]. Our management protocol for PNI is based essentially on hemodynamic and airway status, together with the physical examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The setting of this study is a high‐volume trauma center (~11,000 patients/year) managing a very high number of penetrating trauma victims (~200 PNI/year). Mandatory neck exploration results in a high negative rate (30–89%) in asymptomatic patients [2, 3, 9, 12]. Our management protocol for PNI is based essentially on hemodynamic and airway status, together with the physical examination.…”
Section: Discussionmentioning
confidence: 99%
“…While some clinicians advocate mandatory neck exploration for asymptomatic patients with PNI [1], selective nonoperative management (SNOM) has slowly gained favor [2][3][4][5][6]. The routine application of specialized diagnostic investigations, some of which are invasive, for stable, asymptomatic patients remains controversial [4,5,[7][8][9][10][11][12][13]. The aim of the present study was to validate a protocol of SNOM of PNI based on history and physical examination, findings of which determine further investigations and management.…”
Section: Introductionmentioning
confidence: 99%
“…There has not yet been a consensus on this. Surgical exploration of all neck injuries beyond the platysma muscle significantly reduced mortality during World War II [ 3 ], but 89% of interventions did not identify deep visceral injuries [ 4 ]. In 1969, Monson et al divided the cervical region into the three zones used in the management of trauma diagnostic protocol [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Continuing experience has confirmed that even patients with modest or moderate symptoms or signs, especially with stab wounds in Zone II, will only have a ''therapeutic'' cervical exploration 55-65 % of the time. Therefore, a selective rather than a mandatory operative approach is the standard of care in asymptomatic patients and in those with modest or moderate symptoms or signs [11][12][13].…”
Section: Zone Imentioning
confidence: 99%